The absolute, ultimate guide to Lehninger principles of biochemistry : - Osgood, Marcy (W.H. Freeman and Company, 2009)
Combines an innovative study guide with a reliable solutions manual (providing extended solutions to end-of-chapter problems) in one volume. It includes for each chapter: major concepts, 'What to Review' questions, discussion questions, and self-test questions.